SEJARAH PERKEMBANGAN HUKUM ISLAM DI INDONESIA - Abu Bakar (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
To develop the process of transforming Islamic law into the supremacy of national law, the participation of all relevant parties and institutions is required, as is the case with the relationship between Islamic law and state power bodies which refers to established legal political policies (adatrechts politiek). The legal politics is a product of interaction among political elites based on various socio-cultural groups. When Islamic political elites have strong bargaining power in political interactions, the opportunities for the development of Islamic law to be transformed are even greater. Observing the historical journey of the transformation of Islamic law, laden with various historical, philosophical, political, sociological and juridical dimensions. In reality, Islamic law in Indonesia has experienced ups and downs along with legal politics implemented by state power. All of this, rooted in the socio-cultural strength of the majority of Muslims in Indonesia, has interacted in the political decision-making process, resulting in various political policies for the benefit of the Islamic community. Keywords: history, development, islamic law